Facilitating Accommodation of Learners with Disabilities in Summative Assessment of Literacies in Tanzania through Mobile Application (International Journal of Language, Literacy and Translation, 2025)
Summative Assessment of Language Literacies in Tanzania is administered in the form of a Paper-and-pencil assessment. This kind of assessment hardly accommodates learners with disabilities such as visually impaired ones because it does not allow adjustment of the font size to suit the reader’s needs. As a result, such students might end up being judged as failures in such assessments while their failure is attributed to the nature of the assessment rather than their lack of competence in language literacies. Therefore, to improve the existing situation, the present study investigated the contribution of mobile applications to accommodating learners with diverse needs in taking language literacies assessments. We adopted qualitative action research using interviews, focus group discussion, observation, and reflection as data collection methods from one language teacher and ten standard VII students who were selected purposively. We analyzed data deductively through coding, categorizing, and relating data to available conceptual constructs. Findings show that mobile application makes language assessment more accommodating because of its flexibility in terms of presentation, response delivery, and locations and time given. The study calls for the National examination council in Tanzania to consider the integration of technology in language literacies assessment to maximize the learning opportunities for learners with disabilities. Also, teacher education should empower teachers on the use of technology in their classrooms.